Motivated explanation - Patterson, Richard; Operskalski, Joachim T.; Barbey, Aron K. (Frontiers in Human Neuroscience, 2015)
Although motivation is a well-established field of study in its own right, and has been fruitfully studied in connection with attribution theory and belief formation under the heading of “motivated thinking,” its powerful and pervasive influence on specifically explanatory processes is less well explored. Where one has a strong motivation to understand some event correctly, one is thereby motivated to adhere as best one can to normative or “epistemic” criteria for correct or accurate explanation, even if one does not consciously formulate or apply such criteria. By contrast, many of our motivations to explain introduce bias into the processes involved in generating, evaluating, or giving explanations. Non-epistemic explanatory motivations, or following Kunda's usage, “directional” motivations, include self-justification, resolution of cognitive dissonance, deliberate deception, teaching, and many more. Some of these motivations lead to the relaxation or violation of epistemic norms; others enhance epistemic motivation, so that one engages in more careful and thorough generational and evaluative processes. We propose that “real life” explanatory processes are often constrained by multiple goals, epistemic and directional, where these goals may mutually reinforce one another or may conflict, and where our explanations emerge as a matter of weighing and satisfying those goals. We review emerging evidence from psychology and neuroscience to support this framework and to elucidate the central role of motivation in human thought and explanation.